Hubungan Pengetahuan, Preferensi, Sikap Ibu dan Anak dengan Konsumsi Buah dan Sayur Anak Usia Sekolah RW.016 Kelurahan Kebon Melati - Putri Ayu, (2022)
Fruits and vegetables are important foods that should always be consumed at every meal. Not only for adults, eating fruits and vegetables is also very important to be consumed from the age of children. Lack of fruit and vegetable consumption in school-age children can lead to eye disease, hypertension, obesity, diabetes, cancer, anemia, constipation, lack of concentration in learning, as well as inhibiting the growth and development of children. Overweight and obesity in school-age children resulting from a lack of fruit and vegetable consumption, if left unchecked, will increase the risk of cardiovascular disease in adulthood. This study aims to determine the relationship between knowledge, preferences, attitudes of mothers and about fruit and vegetables with fruit and vegetable consumption of school-age children in RW.016 Kelurahan Kebon Melati. This research used a cross sectional study design which was taken by using a stratified random sampling technique of 100 respondents. Data was collected by filling out questionnaires and SQ-FFQ interviews. Based on the results of statistical tests, there was no relationship between children's knowledge (p=0.122), children's preferences (p=1,000), children's attitudes (p=0.331), and mother's knowledge (p=0.601) with fruit and vegetable consumption of school-age children. There is a relationship between mother's attitude (p=0.040) and mother's preferences (p=0.000) with fruit and vegetable consumption of school-age children.